Subcellular Localization and Rolling Circle Replication of Peach Latent Mosaic Viroid: Hallmarks of Group A Viroids - Bussière, F. (American Society for Microbiology, 1999)
We characterized the peach latent mosaic viroid (PLMVd) replication intermediates that accumulate in infected peach leaves and determined the tissue and subcellular localization of the RNA species. Using in situ hybridization, we showed that PLMVd strands of both plus and minus polarities concentrate in the cells forming the palisade parenchyma. At the cellular level, PLMVd was found to accumulate predominantly in chloroplasts. Northern blot analyses demonstrated that PLMVd replicates via a symmetric mode involving the accumulation of both circular and linear monomeric strands of both polarities. No multimeric conformer was detected, indicating that both strands self-cleave efficiently via their hammerhead sequences. Dot blot hybridizations revealed that PLMVd strands of both polarities accumulate equally but that the relative concentrations vary by more than 50-fold between peach cultivars. Taken together these results establish two hallmarks for the classification of viroids. Group A viroids (e.g., PLMVd), which possess hammerhead structures, replicate in the chloroplasts via the symmetric mode. By contrast, group B viroids, which share a conserved central region, replicate in the nucleus via an asymmetric mechanism. This is an important difference between self-cleaving and non-self-cleaving viroids, and the implications for the evolutionary origin and replication are discussed.